Performance Determination By Training, Workload and Compensation - Yuni Indah Sari; Didin Hikmah Perkasa; Nur Vitriani; Achmad Tarmizi; Siti Annisa Wahdiniawati (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2025)
This study aims to determine and analyze the effect of training, workload and compensation on employee performance with a study at PT Inti Trio Bhakti Jaya. The research design uses a casual quantitative method, namely knowing the effect between the variables studied. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via Google form to employees of PT Inti Trio Bhakti Jaya. This study involved 70 respondents who were the total number of employees of PT Inti Trio Bhakti Jaya. Data analysis was carried out using Smart-PLS (Partial Least Square). Using a Likert scale with a range of 1-5 as a measurement. The results showed that Training is not significant to employee performance, Workload has a positive and significant effect on employee performance, and Compensation is not significant to Employee Performance.